EFEITO DA DENSIDADE POPULACIONAL EM MILHO PELO EMPREGO DE CARACTERES CORRELACIONADOS - Vezzosi, Leandro F.; Gaviraghi, Fernando; Martins, João A. K.; Zambonato, Felipe; Wagner, Juliano F.; Battisti, Gabriel K.; Krüger, Cleusa A. M. B.; Fernandes, Sandra B. V.; Berto, Jorge; Silva, José A. G. d. (Salão do Conhecimento, 2013)
Resumo